ANALISIS FAKTOR – FAKTOR YANG BERPENGARUH TERHADAP PERILAKU PERAWAT DALAM PENGGUNAAN SIMRS DI RSUD KABUPATEN KARANGANYAR - Muhlizardy Muhlizardy; Meila Nissa Solihah; Husnaa Dian Puspita (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2022)
The main objective of the Hospital Management Information System (HMIS) is to improve efficiency, effectiveness, and integration capabilities in health services, starting from outpatient services, inpatient services, emergency departments, surgical installations, medical records, nutrition units, and to management. hospital financial accounting. So it is necessary to optimize the use of HMIS will be an effort to improve the quality and quality of services from hospitals. The purpose of this study was to determine the factors that influence the behavior of nurses in the use of HMIS in Karanganyar District Hospital. This research is a quantitative research using a cross sectional design. The number of samples used was 67 respondents. The technique of collecting samples by random sampling. The analytical method used is multiple linear regression test. From the results of the t-test, it shows that the variable complexity of the tool and motivation has the same value, namely: P-value = 0.000 <0.05, which means that there is a significant influence on the behavior of nurses. While the knowledge and attitude variables had no effect on the behavior of nurses with P-values ​​of 0.109 < 0.05 and 0.134 < 0.05, respectively. For the simultaneous influence of knowledge, attitude, tool complexity, and motivation variables on behavior is 0.000 < 0.05.